2009
DOI: 10.14330/jeail.2009.2.1.10
|View full text |Cite
|
Sign up to set email alerts
|

What can International Law Learn from Indian Mythology, Hinduism and History?

Abstract: Modern India has been rather silent on its role in international law. This reticence remains unexplained in the comparative

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Scholars have suggested that in ancient Indian all the activities were guided by the four goals of dharma (concern for social order or religion), artha (wealth), karma (pleasure) and moksa (deliverance from travails of life, or spiritualism) (Sharma, 2009). Dharma remained perhaps the central aspect of community in Ancient India (Singh & Singh, 2009). Meaning of dharma had a very close relationship with the Hindu philosophical thought and social structure and was created for the wellbeing of all creation.…”
Section: Ancient Indian Visions On Lawmentioning
confidence: 99%
See 1 more Smart Citation
“…Scholars have suggested that in ancient Indian all the activities were guided by the four goals of dharma (concern for social order or religion), artha (wealth), karma (pleasure) and moksa (deliverance from travails of life, or spiritualism) (Sharma, 2009). Dharma remained perhaps the central aspect of community in Ancient India (Singh & Singh, 2009). Meaning of dharma had a very close relationship with the Hindu philosophical thought and social structure and was created for the wellbeing of all creation.…”
Section: Ancient Indian Visions On Lawmentioning
confidence: 99%
“…As the key adviser of Chandragupta Maurya (317-293 B.C), he defeated the Nanda kings, stopped the advance of Alexander's successors, and for the first time ever in the history of ancient India, united most of the Indian subcontinent into the Magadha Empire. The Mauryan Empire was vast and was the first empire in archaeologically recorded history to rule most of the Indian subcontinent with borders extending to Afghanistan (Singh & Singh, 2009). Kautilya work makes a great advance upon the branch of State Law, i.e.…”
Section: Law Arthashastra and Kautilyamentioning
confidence: 99%